La Vacca : Regioni Esterne del Corpo, Scheletro, Sistema Vasale, Muscoli, Organi Interni - Mico, Dott. (1924)
Italian-language book on the anatomy of dairy cattle. It includes a color illustration of a dairy cow that is composed of two large, double-sided flaps and a series of smaller flaps, each of which lifts to reveal the anatomical layer beneath it, from the cow's outer body to its skeleton, vascular system, muscles, and internal organs.
Keywords: Cattle--Anatomy; Cattle; Dairy cattle; Lift-the-flap books; Livestock; Agricultural education